Customer Loyalty Analysis of Hisana Fried Chicken, Medan Johor, Medan City Based on Price and Service Quality - Rinaldi Batubara; Hardi Mulyono; Abd. Rasyid Syamsuri; Lukman Nasution (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study intends to examine how customer loyalty is impacted by price and service quality at Hisana Fried Chicken in Medan Johor, Medan City. This study used a quantitative methodology. From April to September 2022, six months of this study were dedicated to its execution. Utilized data collection methods included questionnaires, documentation study, and observation. 524 consumers in April 2022 made up the study's population. In this investigation, samples were drawn using the probability sampling technique and the Slovin formula. 84 customers in total participated in this survey as responders. Multiple linear regression using the statistical product software solution (SPSS) program is the analytical approach used in this study. The study's findings demonstrate that, price has a positive and significant impact on consumer loyalty at Hisana Fried Chicken in Medan Johor, Medan City. Customer loyalty at Hisana Fried Chicken in Medan Johor, Medan City, is positively and significantly impacted by service quality. The results also demonstrated a positive and significant relationship between price and service quality and customer loyalty at Hisana Fried Chicken in Medan Johor, Medan City. According to this study's coefficient of determination (R2), which is 0.594, pricing and service quality factors can account for 59.4% of consumer loyalty. Keywords: Price, Service Quality, Customer Loyalty.